English as an additional language and educational achievement in England: An analysis of the National Pupil Database - Strand, S; Malmberg, L; Hall, J (Educational Endowment Fund, 2015)
The project was commissioned by three charitable groups – the Education Endowment Foundation (EEF), Unbound Philanthropy and The Bell Foundation – to analyse the evidence from national data in England on the achievement of students with English as an Additional Language (EAL) and to review the literature on effective interventions to raise the attainment of pupils with EAL. The key questions addressed by the project were: Who are the most at-risk groups of EAL learners and what are the predictors of low attainment for these learners? What are the most promising programmes and interventions to address EAL achievement gaps on the basis of causal evidence? This report presents an analysis of the most recent England National Pupil Database (NPD) from 2013 with respect to the first question above. A sister report focuses on the second question concerning effective interventions and is published in parallel with this report. The overall purpose of the project is to help schools and policymakers to effectively target policy, interventions and funding to address achievement gaps.